2017
DOI: 10.1159/000481226
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Suturing Closure Is Recommended after Endoscopic Treatment of Colorectal Tumors in Patients with Antiplatelet/Anticoagulant Therapy

Abstract: The prophylactic closure of mucosal defects after endoscopic resection is known to prevent postoperative bleeding in colorectal lesions. However, closure of large mucosal defects is difficult with conventional clips only, and several closure techniques have been previously described; use of an Endoloop, 8-ring loop, or loop clip and a small incision around the mucosal defect. Given that the prophylactic closure requires much cost and time, the application should be limited to high-risk cases. Medication of ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 3 publications
(3 reference statements)
0
7
0
Order By: Relevance
“…Adverse events (AEs) related to endoscopic tissue resection include perforation and bleeding. Previous studies have reported decreased post-procedure bleeding and perforation with use of resection site closure [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Adverse events (AEs) related to endoscopic tissue resection include perforation and bleeding. Previous studies have reported decreased post-procedure bleeding and perforation with use of resection site closure [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several previous studies reported that closure of mucosal defects with clips after EMR for large colorectal lesions decreased the risk of bleeding after ER [39,40]. Several techniques, such as endoloop [41], hand-suturing [42], OverStitch endoscopic suturing [43], 8ring [44], mucosal incision [45], over-the-scope clip [46], and two-channel techniques [47], for complete closure of large, resected ulcers after ER have been demonstrated. The tissue shielding method using a polyglycolic acid (PGA) sheet and fibrin glue may effectively prevent bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…been reported [51][52][53][54][55]. These techniques should only be used in complex clipping cases by expert endoscopists.…”
Section: Tts Clipmentioning
confidence: 99%
“…allow adequate closure of large lesions will likely become standard practice, competing with the expensive treatment with large-diameter clips. Case reports and series have reported several of these techniques, using clips in combination with snares and nylon lines [51][52][53]55,58].…”
Section: Improvementmentioning
confidence: 99%